2012
DOI: 10.1021/ja306992k
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed C–H Activation Taken to the Limit. Flattening an Aromatic Bowl by Total Arylation

Abstract: All 10 C-H positions on the rim of corannulene can be arylated by repetitive palladium-catalyzed C-H activation. To relieve congestion among the 10 tightly packed aryl substituents in the product, the central corannulene adopts a nearly planar geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
53
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 34 publications
4
53
0
1
Order By: Relevance
“…Upon repeated subjection of corannulene (88) to the arylation reaction conditions, decaphenylcorannulenes 89-91 were obtained in variable yield (Scheme 22). [68] In contrast to the [n]acenes where multiple arylation forces the [n]acene core to twist out of planarity, [69] the corannulene system was forced to flatten to relieve the congestion between tightly bunched aryl groups. The observed (X-ray) bowl depth of the corannulene moiety in 91 is only 0.25 Å (cf.…”
Section: Arylation Reactionsmentioning
confidence: 99%
“…Upon repeated subjection of corannulene (88) to the arylation reaction conditions, decaphenylcorannulenes 89-91 were obtained in variable yield (Scheme 22). [68] In contrast to the [n]acenes where multiple arylation forces the [n]acene core to twist out of planarity, [69] the corannulene system was forced to flatten to relieve the congestion between tightly bunched aryl groups. The observed (X-ray) bowl depth of the corannulene moiety in 91 is only 0.25 Å (cf.…”
Section: Arylation Reactionsmentioning
confidence: 99%
“…Compared to metal-catalyzed functionalization of 52, decaaryl-substituted corannulenes 57 were prepared by repetitive palladium-catalyzed arylation of corannulene with arylboroxin through C-H activation (Scheme 15) [74]. It was observed that the arylation was not stopped at decaphenylcorannulene 57 (Ar¼Ph) when phenylboroxin was employed, whereas (4-tert-butylphenyl)boroxin and (4-chlorophenyl)boroxin prevent the overarylation and allow decakis(4-tert- [100].…”
Section: T-bu T-bu T-bu T-bu T-bumentioning
confidence: 99%
“…All of these experimental and theoretical investigations strongly indicate that, unlike the case of corannulene, 17 the structural and dynamic properties of sumanene can be retained even upon arylation at all the peripheral aromatic carbons. Based on the computational optimization ( Figure S2b), all the phenyl rings attached to the six peripheral aromatic carbons of 3a are expected to adopt a geometry vertical to the sumanene skeleton, as in the case of deca-arylated corannulene.…”
mentioning
confidence: 96%
“…17 Similarly, Amaya, Hirao, and co-workers reported that the introduction of bulky 1,1,4,4-tetramethylbutane-1,4-diyl groups at the peripheral aromatic carbons of sumanene also makes the bowl depth shallower. 12 These reports motivated us to investigate the bowl depth and the π-orbital axis vector (POAV) angle at the hub carbons 18 of 1, 2, and hexaphenylsumanene 3a (Table 2).…”
mentioning
confidence: 96%
See 1 more Smart Citation